2002
DOI: 10.1128/jvi.76.20.10393-10400.2002
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 and BAX Protect Adult Mice from Lethal Sindbis Virus Infection but Do Not Protect Spinal Cord Motor Neurons or Prevent Paralysis

Abstract: Cellular proteins that regulate apoptotic cell death can modulate the outcome of Sindbis virus (SV) encephalitis in mice. Both endogenous and overexpressed BCL-2 and BAX proteins protect newborn mice from fatal SV infection by blocking apoptosis in infected neurons. To determine the effects of these cellular factors on the course of infection in older animals, a more neurovirulent SV vector (dsNSV) was constructed from a viral strain that causes both prominent spinal cord infection with hind-limb paralysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 22 publications
(34 reference statements)
3
28
0
Order By: Relevance
“…However, it is possible that prodeath BCL-2 family proteins are not only latent death factors but also carry out important functions in healthy cells. Consistent with this idea, BAX and BAK can function as potent anti-death factors in cultured neurons and in mouse models (1)(2)(3)(4). This dual function of BAK may be explained by its ability to decrease neuronal excitability in healthy neurons because this function is consistent with both its ability to promote death during development (based on the phenotype of double Bax/ Bak knock-out mice) and to inhibit death induced by excitotoxic stimuli in postnatal animals (4,5).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…However, it is possible that prodeath BCL-2 family proteins are not only latent death factors but also carry out important functions in healthy cells. Consistent with this idea, BAX and BAK can function as potent anti-death factors in cultured neurons and in mouse models (1)(2)(3)(4). This dual function of BAK may be explained by its ability to decrease neuronal excitability in healthy neurons because this function is consistent with both its ability to promote death during development (based on the phenotype of double Bax/ Bak knock-out mice) and to inhibit death induced by excitotoxic stimuli in postnatal animals (4,5).…”
supporting
confidence: 52%
“…Viruses and Animals-Coding sequences for wild type and mutant BAD were subcloned from pSG5/pDB59 into the Sindbis virus vectors dsTE12Q (for infection of newborn mice) and dsNSV (for infection of 5-week-old mice) (3,25) or into the retrovirus construct pLXSN (26) for generating recombinant viruses. Control Sindbis viruses contain the reverse (non-coding) orientations of mBAD L , viral KSBcl-2, or other irrelevant cDNA of similar size to ensure equivalent replication rates between viruses by maintaining the same genome size in experimental and control viruses.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, OK-92 had a strong CPE after SIN infection, but Ras activation was very weak in this cell line. A number of studies suggest that apoptosis is important in viral CPEs and the mechanism of SIN-induced apoptosis may be related to members of the caspase family and Bcl-2 proteins (Nava et al, 1998;Kerr et al, 2002). Our study showed that cell death in HSC-3 cells, the most susceptible of the cell lines to SIN, was induced by apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…Elegant studies have shown that Sindbis virus infection triggers distinct neuronal-death pathways that vary according to the subtype and maturation state of the neurons (11). Mortality in Sindbis virus-infected neonatal mice was reduced by overexpression of cell death regulatory proteins, including Bcl-2, Bax, CrmA, and beclin-1 (26)(27)(28)35), whereas Bcl-2 and Bax expression in adult mice protected hippocampal but not spinal cord neurons from virus-induced death (18). Although further study is warranted, we speculate that different neurons may undergo cell-specific death programs in response to WNV infection.…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathomentioning
confidence: 99%